Pulmonary diffusing capacity among individuals recovering from mild to moderate COVID-19: a cross-sectional study - Dana Yelin; Nassem Ghantous; Muhammad Awwad; Vered Daitch; Talya Kalfon; Michal Mor; Shira Buchrits; Yair Shafir; Irit Shapira-Lichter; Leonard Leibovici; Dafna Yahav; Ili Margalit; et al. (Scientific Reports)
Abstract Impaired pulmonary diffusing capacity for carbon monoxide (DLCO) following COVID-19 has been consistently reported among individuals recovering from severe-critical infection. However, most long COVID cases follow non-severe COVID-19. We assessed DLCO among individuals with long COVID recovering from mild to moderate acute illness. A cross-sectional study of adults with long COVID, assessed at a COVID recovery clinic > 3 months following the onset of acute infection, during 2020–2021. Participants subjectively ranked their dyspnea severity based on its impact on their daily living and underwent comprehensive pulmonary function testing (PFT). Clinical correlates for impaired DLCO (defined as < 80%) were assessed using multivariable logistic regression models. A total of 458 individuals, their mean age 45 (SD 16) and 246 (54%) of whom are women, were evaluated at an average of ~ 4 months following acute COVID-19. The most frequent PFT impairment was reduced DLCO, identified among 67 (17%) of the cohort. Clinical correlates of impaired DLCO included women (odds ration [OR] 3.64, 95% confidence interval [CI] 1.78–7.45, p < 0.001), cigarette smoking (OR 2.25, 95% CI 1.14–4.43, p = 0.019), and moderate-severe dyspnea (OR 2.77, 95% CI 1.39–5.50, p = 0.004). BMI inversely correlated with DLCO (OR 0.90, 95% CI 0.85–0.96 per 1 unit, p = 0.002). Impaired DLCO was not uncommon among individuals recovering from mild to moderate COVID-19. Women are at a greater risk, and subjective dyspnea correlated with impaired DLCO. Clinicians can rely on self-reported significant dyspnea to guide further assessment.